Indera Keenam Dan Stigma Pada Tokoh-Tokoh Dalam Manga Saikometoraa Eiji Karya Yuma Ando - Suastini Kusumawati, Ni Putu (Humanis; Vol 21 No 1 (2017), 2017)
The title of this research is “The Sixth Sense and Stigma on the Figures in Manga Saikometoraa Eiji by Yuma Ando”. The aims of this research are to know the sixth sense forms and the reactions of other figures to the figures who have the sixth sense. This research used the literary psychology theory by Wellek and Warren (1993), Extra Sensory Perception theory by JB. Rhine (1997), and semiotics theory by Marcel Danesi (2010) and Scout McCloud (2008). The results of this research showed that there were two forms of sixth sense that owned to four figures. The sixth sense form that were precognition by the figure Eiji, Ikushima and Akagi, while the retrocognition was owned by the figure Eiji and Tatsuhiko. How to get information through the ability of the sixth sense that were, precognition by used of intuition, dreams, and Psychometry, while the retrocognition by used of Psychometry and Mediumship. There were two types of figures based on their nature that showed the reaction to the figures who has the ability of the sixth sense, that were protagonist and antagonist. Protagonist tends to showed a positive reaction to the figures who has the ability of the sixth sense, while the antagonist tends to showed a negative reaction to the sixth sense ability owned by the figures.